Relative age effect in Turkish soccer - Hacer Mulazımoglu; Kerimhan Kaynak; Mehmet Bayansalduz; Olcay Mulazımoglu (Türk Spor ve Egzersiz Dergisi)
Relative Age Effect (RAE) refers to the difference between the individuals who were born in the early or the later period of the same year. The purpose of this study was to investigate the existence and prevalence of RAE in Turkish Soccer. The data were collected from 3074 (530 professional players and 2544 amateur players) active players who play for eight different age categories of 19 soccer clubs in Turkish First Soccer League. The significance of the distributions by birth month, distributions by quarter-year and the differences between groups were analyzed through chi-square test. For all categories, first month (January%=22.10), and first quarter (Q1%=44.44) of distributions by birth month and were found to be significantly high (p lt;0.01). The researchers observed the existence and prevalence of RAE in youth and professional teams of Turkish Soccer Clubs. Trainers should evaluate players carefully during talent selection, in order to eliminate this unfair competition.